"Wearing My Spiritual Jacket": The Role of Spirituality as a Coping Mechanism Among African American Youth. (October 2017) - Dill, LeConté J.
There is growing evidence in the theoretical literature regarding the importance of religion and religiosity in people's lives, particularly concerning their health and well-being. Spirituality, a related but different concept, has been less well studied, especially empirically, but shows promise as a mechanism for coping with deleterious social and health circumstances. This article details a qualitative exploration of the role of spiritual coping in the lives of urban African American youth. Data were gathered through in-depth, semistructured interviews with 20 African American youth, ages 12 to 20 years. The findings indicate that urban African American youth have multifaceted dimensions of their spirituality, including the role of prayer in their lives, an unwavering faith in a higher power, and the importance of giving back to their communities. Such findings offer counterstories, generated through ethnographic research, to the dominant discourses regarding urban African American youth. Ultimately, this study's findings have implications for research and practice related to the mechanisms of both ill-health and wellness among youth.